The Science and Technology of the Square Kilometre Array - Tingay, Steven (Institute of Physics Publishing, 2014)
I discuss the science and engineering of the Square Kilometre Array (SKA), the next generation astronomical observatory for studying the structure and evolution of the Universe. I give an overview of the SKA Key Science areas and map them onto the instruments that are being developed for these investigations. I outline where the SKA is being built and how the international community is developing the project. I discuss a range of SKA pathfinder and precursor telescopes that are currently being built or are operational, helping to inform SKA engineering, ICT and astrophysics.